Male or Female? - Influence of Gender Role and Sexual Attraction on Sex Categorization of Faces - Luther, Teresa; Lewis, Carolin A.; Grahlow, Melina; Hüpen, Philippa; Habel, Ute; Foster, Celia; Bülthoff, Isabelle; Derntl, Birgit (Frontiers in Psychology, 2021)
The categorization of dominant facial features, such as sex, is a highly relevant function for social interaction. It has been found that attributes of the perceiver, such as their biological sex, influence the perception of sexually dimorphic facial features with women showing higher recognition performance for female faces than men. However, evidence on how aspects closely related to biological sex influence face sex categorization are scarce. Using a previously validated set of sex-morphed facial images (morphed from male to female and vice versa), we aimed to investigate the influence of the participant’s gender role identification and sexual orientation on face sex categorization, besides their biological sex. Image ratings, questionnaire data on gender role identification and sexual orientation were collected from 67 adults (34 females). Contrary to previous literature, biological sex per se was not significantly associated with image ratings. However, an influence of participant sexual orientation and gender role identity became apparent: Participants identifying with male gender attributes and showing attraction towards females perceived masculinized female faces as more male and femininized male faces as more female when compared to participants identifying with female gender attributes and attraction towards males. Considering that we found these effects in a predominantly cisgender and heterosexual sample, investigation of face sex perception in individuals identifying with a gender different from their assigned sex (i.e., transgender people) might provide further insights into how assigned sex and gender identity are related.